FAKTOR YANG MEMENGARUHI KEPUASAN NASABAH BANK MUAMALAT CABANG AMBON - Pary, Gilman (Jurnal Minds: Manajemen Ide dan Inspirasi, 2017)
The purpose of this study is to examine the influence of attribute factors of Islamic products, religious commitment, trust, and quality of service on customer satisfaction, either partially or simultaneously at Bank Muamalat Ambon Branch. The customer in question is the customer of Muamalat Bank Ambon Branch either as a cash custodian or a fund user who has used the services of Bank Muamalat Ambon Branch at least one year. The sample of this research is 73 customers of Bank Muamalat Branch of Ambon, taken by accidental method, that is the determination of sample by chance, anyone who by chance meet with the researcher at the time of data collection can be used as sample. Data analysis techniques use multiple linear regression. The research results show product attributes, religious commitment, service quality and trust together have a positive and significant impact on customer satisfaction of Bank Muamalat Ambon Branch. Product attributes, religious commitment, service quality and trust are able to explain customer loyalty either simultaneously or partially.